The Comparative Analysis of Forgetting and Retention Strategies in Gamification-Based Assessment and Formative-Based Assessment: Their Impact on Motivation for Learning - Sudsom, Udorn; Phongsatha, Thanawan (International Journal of Sociologies and Anthropologies Science Reviews, 2024)
Background and Aim: The study investigates how two assessment methods, gamification-based and formative-based affect motivation for learning and memory retention strategies in the corporate training setting. The primary objective was to compare the effectiveness s these assessment approaches in learning motivation and in forgetting and retention. Materials and Methods: In this study, seventy-six employees working at a duty-free retail store in a Middle Eastern airport took part. The participants were divided into two groups. One group took a gamification-based assessment using Kahoot! application, while the other group took a formative-based assessment. Both groups were evaluated for recall and recognition after learning for one week. After two weeks, the content was reviewed, and recall and recognition tests were conducted using Kahoot! application for relearning. Finally, after the assessment, both groups were given a questionnaire about staff motivation in learning. Results: Gamification has been found to significantly enhance learners' motivation, resulting in improved scores in various areas, including interest-enjoyment, perceived competence, and effort importance. However, it was found that learners felt less tension and pressure. Compared to traditional formative assessments, gamified approaches lead to higher levels of confidence and perceived effort in learning. This method has improved forgetting and retention, demonstrated by higher recall, recognition, and relearning scores. Furthermore, the gamified approach creates a stimulating and challenging learning environment, as decreased tension and pressure indicated. Conclusion: The study's findings support the existing research, indicating that gamification significantly boosts motivation and improves memory retention in corporate training. These insights reveal the complex relationship between emotions and evaluations during the learning process and highlight the potential of gamified methods in corporate training. Further research should explore the underlying mechanisms and their compatibility with the existing literature on memory and learning processes.